Natives and Newcomers: Canada's "Heroic Age" reconsidered - Trigger, Bruce Graham (McGill-Queen's University Press, 1994)
Plusieurs réimpressions
Keywords: Autochtones; Français; Iroquoiens; Iroquois

On the Ruins of Hochelaga: 1535-1650 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Autochtones; Cartier; Jacques; Chomedey de Maisonneuve; Paul (Maisonneuve; Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance; Jeanne; Société de Notre-Dame de Montréal

Sur les décombres d'Hochelaga, 1535-1650 - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Autochtones; Cartier; Jacques; Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance; Jeanne; Société de Notre-Dame de Montréal